2020
DOI: 10.1155/2020/2535843
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABO and Rh Blood Group Phenotypes with Type 2 Diabetes Mellitus at Felege Hiwot Comprehensive Referral Hospital Bahir Dar, Northwest Ethiopia

Abstract: Background. ABO and Rh blood group antigens are thought to be among genetic determinants of type 2 diabetes mellitus. Identification of blood group phenotypes are more associated with type 2 diabetes mellitus. It will be helpful for individuals who are susceptible blood groups to take care of themselves by avoiding other predisposing factors and taking preventive measures. Methods. Hospital-based comparative cross-sectional study was carried out from February to April 2019 at Felege Hiwot Comprehensive Referra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
3
12
1
Order By: Relevance
“…No associations were found of the blood groups A and AB with T2DM (OR = 1.04, 95% CI: 0.97–1.12 and OR = 1.03, 95% CI: 0.92–1.16, respectively) in the present study, consistent with the findings of previous studies performed in western Algeria, 36 India, 62 and Bangladesh, 15 which also showed no associations between the ABO blood groups and T2DM. In contrast, previous studies have shown that individuals with blood group A are more likely to develop T2DM 38,40 and to have higher insulin and random blood glucose concentrations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…No associations were found of the blood groups A and AB with T2DM (OR = 1.04, 95% CI: 0.97–1.12 and OR = 1.03, 95% CI: 0.92–1.16, respectively) in the present study, consistent with the findings of previous studies performed in western Algeria, 36 India, 62 and Bangladesh, 15 which also showed no associations between the ABO blood groups and T2DM. In contrast, previous studies have shown that individuals with blood group A are more likely to develop T2DM 38,40 and to have higher insulin and random blood glucose concentrations.…”
Section: Discussionsupporting
confidence: 91%
“…1 In addition, ABO blood group-related susceptibility to various viral infections, including with hepatitis B, influenza viruses, and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), have been shown in several studies. 45,46 However, only some of the previous studies have shown a link between T2DM and ABO blood group: some have shown no link, 15,20,47,48 whereas others have shown a positive association. 14,33 Therefore, in the present study, we explored the relationships of the ABO and Rh blood groups with T2DM by means of a systematic review and meta-analysis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast to our present results, Nigerian people with O- or A+ blood groups appeared to be at a greater risk of developing DM in the ( 9 ). A study of a population in northwest Ethiopia suggested that antigen B was associated with a greater increased risk of T2DM, whereas a O blood group was associated with a lower risk ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides their clinical significance in the blood transfusion and compatibility, ABO and Rh blood group antigens were found to be associated with many non-infectious and infectious diseases. 2 , 3 Several studies revealed these blood group antigens were associated with diabetes mellitus, hypertension, gastric cancer, duodenal ulcer, breast cancer, malaria, and helicobacter pylori infection. 2 , 4 , 5 Some other studies also reported that ABO and Rh blood group antigens were associated with transfusion-transmitted infections (TTIs), which include Hepatitis B virus (HBV), human immunodeficiency virus (HIV), Hepatitis C virus (HCV), and syphilis.…”
Section: Introductionmentioning
confidence: 99%